(untitled) (Research, Society and Development, 2021)
It is known that horses are potential reservoirs of zoonotic bacteria, such as Escherichia coli and Salmonella sp. However, there is little information on zoonotic bacteria as potential sources of infection and antibiotic resistance. Thus, the present study aimed to verify the prevalence of diarrheagenic E. coli (DEC) in horses from the northern region of Tocantins, Brazil and determine the microorganism’s susceptibility to the main antimicrobials used in horses and humans. By transrectal palpation, stool samples were taken from 72 horses health, and E. coli was identified by biochemical tests. To detect the main DEC serogroups, the slide agglutination technique was performed. The susceptibility to antimicrobials followed the methodology recommended by the Clinical and Laboratory Standards Institute (2011) and the National Committee for Clinical Laboratory Standards (2015). E. coli was detected in 39 of the studied animals and 68 different strains were identified, 32 (47.06%) of which were DEC. Of these, 26 (81.25%) were enteropathogenic, 5 (15.62%) enteroinvasive, and 1 (3.13%) enterohemorrhagic, which reflects the role of equines as reservoirs of pathogenic strains and as source infection to other animals and humans, representing an important threat to public health. Regarding antimicrobial resistance, the highest in vitro sensitivity and resistance was for Ciprofloxacin/Meropenem and Penicillin G, respectively. Multidrug-resistant isolates were also identified, with predominant resistance to ß-lactams, tetracyclines and sulfonamides. It is concluded that equines are potential reservoirs of pathogenic E. coli. An antibiogram is an important tool for the choice of an effective antimicrobial in cases the colibacillosis. People who have contact with equines should pay attention to the possible transmission of these pathogens during management.